Comparison of two yttrium-90 regimens in inflammatory and osteoarthropathies. Issue 2 (February 1992) - Will, R; Laing, B; Edelman, J; Lovegrove, F; Surveyor, I
Abstract : Two yttrium-90 (90Y) radiosynovectomy procedures were compared. One procedure, performed at the Royal Perth Rehabilitation Hospital (RPRH) required a shorter immobilisation time than that performed at the Sir Charles Gardiner Hospital (SCGH). There were no significant differences in outcome between the two procedures for the groups with inflammatory and osteoarthropathy. Thirty two patients (45 joints) with inflammatory arthropathy were treated (25 with rheumatoid arthritis, three with psoriatic arthritis, two with ankylosing spondylitis, and two with unspecified inflammatory arthropathy) and 40 patients (58 joints) with osteoarthropathy. A separate assessment of local lymph node spread in patients treated by the RPRH showed a minor spread of 90Y in one of 37 joints assessed. A marked improvement in the patient evaluation scores in the inflammatory arthropathy group at three months persisted at 12 months. Good lasting responses were more common in patients with inflammatory arthropathy with a normal joint or early radiological disease. A marked improvement in the pain and evaluation scores occurred at three months in the group with osteoarthropathy but had disappeared by six months after treatment.